Synthesis of indium-catalyzed Si nanowires by hot-wire chemical vapor deposition - Chong, S.K.; Goh, B.T.; Aspanut, Z.; Muhamad, M.R.; Dee, C.F.; Rahman, S.A. (2011)
Indium (In) catalyzed silicon nanowires (SiNWs) were synthesized by using hot-wire chemical vapor deposition (HWCVD) technique. Indium droplets were deposited on Si substrates by hot-wire evaporation of In wire, which was immediately followed by the growth of SiNWs from the droplets. Three sets of samples were prepared by varying the length of In wires, l, as 3, 1 and 0.5 mm. The sizes of In catalyst droplets decreased from 271.4 +/- 66.8 to 67.4 +/- 16.6 nm when the l was reduced from 3 to 0.5 mm. Larger size of In droplets (271.4 +/- 66.8 nm) was found to induce the growth of worm-like NWs. The decrease in size of In catalyst droplets induced the formation of aligned and tapered NWs with smaller tips. The smallest value of tapering parameter, T-p of 40.5 nm/mu m is correlated to the SiNWs induced by the smallest size of In droplets (67.4 +/- 16.6 nm). The as-grown SiNWs showed high purity and good crystalline structure. (C) 2011 Elsevier B.V. All rights reserved.